PENGARUH KOMPENSASI DAN KESELAMATAN DAN KESEHATAN KERJA (K3) TERHADAP KEPUASAN KERJA PADA KARYAWAN PT. LAJU PERDANA INDAH (LPI) DI KABUPATEN OKU TIMUR - Novitasari, Novitasari; Wihana, Wihana; Solikhan, Solikhan (AKTUAL, 2024)
This research aims to determine the effect of compensation and occupational health and safety (K3) on job satisfaction among employees at PT. Laju Perdana Indah (LPI) Kab. East OKU. The research method used is a quantitative approach with a descriptive research design. The data collection method uses a questionnaire on compensation, occupational health and safety, and job satisfaction with a Likert scale model. The subjects in this research involved 134 employees. The research results show that there is a very positive and significant influence between compensation and occupational health and safety on job satisfaction among employees at PT. Laju Perdana Indah (LPI) Kab. East OKU. Apart from that, based on a simple regression analysis model, it shows that there is a positive and significant influence of compensation on job satisfaction. Then there is a positive and very significant influence between occupational health and safety on job satisfaction.